An insider's guide to refinancing your mortgage - Reed, David
For many homeowners, refinancing a mortgage can save them significant money, considerably reducing their monthly payments. It can also give them breathing space to pay off debts or allow them to make other investments, pay for college, or finance home improvements. An Insider's Guide to Refinancing Your Mortgage is dedicated to an often-misunderstood aspect of mortgage lending: refinancing a mortgage loan. Readers will learn why to refinance, when to finance, as well as how to find the best lender, loan officer, and rate. Mortgage expert David Reed takes readers step bystep through the refinance process and shows them how to evaluate their current loan program and compare it with other options. By following Reed's invaluable advice, homeowners will learn: when a refinance is right for them - how to lock in the absolute lowest rate at the lowest cost - how the mortgage process works from the inside - how loan officers get paid - how to identify and avoid predatory lenders - how to negotiate closing costs An Insider's Guide to Refinancing Your Mortgage will save readers money and heartache when negotiating a loan.